HUBUNGAN ANTARA LUAS LAHAN PERTANIAN DENGAN PRODUK DOMESTIK REGIONAL BRUTO SEKTOR PERTANIAN DI KOTA TOMOHON - Aditya Novandy Arotaa; Benu L.S. Olfie; Theodora M. Katiandagho (AGRI-SOSIOEKONOMI, 2016)
Tomohon development as an autonomous region led to the need for non-agricultural land is increasing from time to time. This condition causes the competition has taken place in land use. Feared an increased need for non-agricultural land will lead to land conversion of agricultural land to non-agricultural. The transfer of land use will have an impact on agricultural production that will affect the agricultural sector GDP. This study aims to determine the relationship between the area of ​​agricultural land with a regional gross domestic product of agriculture in Tomohon. This study was conducted over four months starting in February 2015 to May 2015 in Tomohon. The data are used, in this study, is a secondary data obtained from the Office of National Statistics Agency (BPS) and the Department of Agriculture in To-mohon. Data presented tabularize and and analyzed using correlation analysis. The results showed that, in the last three years, agricultural land area in Tomohon shrinkage due to the need for non-agricultural land, especially residential construction increased. It is given Tomohon is a city that is building. Reduction of agricultural land in 2012 amounted to 1.77 percent by the year 2014 decreased by 0, 01 percent. Instead rate of growth of gross regional domestic product of the year 2012 increased by 6.54 percent to 6.92 percent in 2014. The study concluded that the impact of agricultural land being against the gross regional domestic product, caused by another factor, namely the constant price factors that influence regional gross do-mestic product of Tomohon. Thereforet, when the land area or size increased in 2005-2011 and decreased in the year 2012 - 2014 however regional gross domestic product still increased. The relationship between land area with a regional gross domestic product is being categorized correlated with the value of the correlation is 0.62.*er*